2018
DOI: 10.1111/ijcs.12432
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumers’ purchase intention towards green products in an emerging market: The role of consumers’ perceived readiness

Abstract: Consumers’ awareness of green products has increased in the last few years, but studies show that the demand for green products has been stagnant. The purpose of this study is to explore the roles of consumers’ perceived readiness to be green and subsequently, how readiness to be green affects consumers’ purchase intention towards green products in an emerging market, Indonesia. A total of 916 survey responses were collected in three universities, two major shopping malls and several housing areas in Yogyakart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(156 citation statements)
references
References 107 publications
(150 reference statements)
7
144
1
4
Order By: Relevance
“…In literature, one of the important areas of interests of the TPB was suggested as leisure behaviors that consist of tourism activities (Ajzen & Driver, ), and there have been many studies showing that the TPB supported intentions to use green products (Hsu, Chang, & Yansritakul, ; Yadav & Pathak, ; Yadav & Pathak, ). Over the last decade, the original TPB constructs were used for understanding customers' green purchase intentions (Albayrak, Aksoy, & Caber, ; Arli, Tan, Tjiptono, & Yang, ; Vermeir & Verbeke, ; Wiederhold & Martinez, ). In literature, the TPB was represented as a reliable model for predicting intentions to green products (Kalafatis et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, one of the important areas of interests of the TPB was suggested as leisure behaviors that consist of tourism activities (Ajzen & Driver, ), and there have been many studies showing that the TPB supported intentions to use green products (Hsu, Chang, & Yansritakul, ; Yadav & Pathak, ; Yadav & Pathak, ). Over the last decade, the original TPB constructs were used for understanding customers' green purchase intentions (Albayrak, Aksoy, & Caber, ; Arli, Tan, Tjiptono, & Yang, ; Vermeir & Verbeke, ; Wiederhold & Martinez, ). In literature, the TPB was represented as a reliable model for predicting intentions to green products (Kalafatis et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the last decade, the original TPB constructs were used for understanding customers' green purchase intentions (Albayrak, Aksoy, & Caber, 2013;Arli, Tan, Tjiptono, & Yang, 2018;Vermeir & Verbeke, 2006;Wiederhold & Martinez, 2018). In literature, the TPB was represented as a reliable model for predicting intentions to green products (Kalafatis et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the food hawkers' actual behavior is concerned with the intention to use EFFP in their business activities. It has been observed that the food hawkers' reluctance to use of EFFP is because they lack the readiness in their minds (Arli et al, 2018;Han et al, 2011). The environment (De Hoop & Jehlička, 2017) and the intrinsic factor (Giffin & Lombrozo, 2018;Van der Werff et al, 2013) have also affected the factor intention to use of EFFP among the food hawkers.…”
Section: Actual Behavior Of Environmentally Friendly Food Packagingmentioning
confidence: 99%
“…Additionally, perceived behavioral control lies in the gap of the relationship issue of the study. This occurs in view of the market condition (Arli et al, 2018), ability (Hansen et al, 2018), and information of the sources (Hajli & Lin, 2016) that remain the paradox of the situation among food hawkers. Thus, the vision of that issue would substantiate for the matter for intention to use EFFP among food hawkers.…”
Section: Actual Behavior Of Environmentally Friendly Food Packagingmentioning
confidence: 99%
“…The literature review distinguished several motives for green consumption. The majority of them was tested in the context of developed economy, where the green market has left its nascent stage (Arli et al, 2018). However, the global green growth cannot be ensured without the involvement of developing countries in this direction (Al Mamun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%